Sexual dysfunction, mood, anxiety, and personality disorders in female patients with fibromyalgia - Kayhan F; Kucuk A; Satan Y; İlgün E; Arslan; Ilik F (Neuropsychiatric Disease and Treatment)
Fatih Kayhan,1 Adem Küçük,2 Yılmaz Satan,3 Erdem İlgün,4 Şevket Arslan,5 Faik İlik6 1Department of Psychiatry, Faculty of Medicine, Selçuk University, 2Department of Rheumatology, Faculty of Medicine, Necmettin Erbakan University, 3Department of Psychiatry, Konya Numune State Hospital, 4Department of Physical Therapy and Rehabilitation, Faculty of Medicine, Mevlana University, 5Department of Internal Medicine, Faculty of Medicine, Necmettin Erbakan University, 6Department of Neurology, Faculty of Medicine, Başkent University, Konya, Turkey Background: We aimed to investigate the current prevalence of sexual dysfunction (SD), mood, anxiety, and personality disorders in female patients with fibromyalgia (FM). Methods: This case–control study involved 96 patients with FM and 94 healthy women. The SD diagnosis was based on a psychiatric interview in accordance with the Diagnostic and Statistical Manual of Mental Disorders, fourth edition criteria. Mood and anxiety disorders were diagnosed using the Structured Clinical Interview. Personality disorders were diagnosed according to the Structured Clinical Interview for DSM, Revised Third Edition Personality Disorders. Results: Fifty of the 96 patients (52.1%) suffered from SD. The most common SD was lack of sexual desire (n=36, 37.5%) and arousal disorder (n=10, 10.4%). Of the 96 patients, 45 (46.9%) had a mood or anxiety disorder and 13 (13.5%) had a personality disorder. The most common mood, anxiety, and personality disorders were major depression (26%), generalized anxiety disorder (8.3%), and histrionic personality disorder (10.4%). Conclusion: SD, mood, and anxiety disorders are frequently observed in female patients with FM. Pain plays a greater role in the development of SD in female patients with FM. Keywords: anxiety, depression, fibromyalgia, sexual dysfunction